Group Conseling with Self-Instruction Techniques and Cognitive Restructuring Techniques to Reduce Academic Anxiety (Jurnal Bimbingan Konseling, 2018)
The purpose of this research was to examine the effectiveness of counseling in the group of self-instruction techniques and cognitive restructuring techniques to reduce students' academic anxiety. This research uses 2 x 2 Factorial Design, applied to students as many as 31 students in Public Senior High School 12 Semarang. The instrument used was the Academic Achievement Questionnaire with a sub-scale of learning-related anxiety, class-related anxiety and test anxiety. Data analysis techniques used are 2-way ANAVA test and the mean difference. The results showed that counseling in the group of self-instruction techniques and cognitive restructuring techniques were effective to reduce students' academic anxiety. The findings of this research prove the effectiveness of group counseling services with self-instruction techniques and cognitive restructuring techniques for students in the city of Semarang Indonesia.